Electronic dashboard‐based remote glycemic management program reduces length of stay and readmission rate among hospitalized adults. Issue 9 (20th February 2021) - Sheen, Yi‐Jing; Huang, Chien‐Chung; Huang, Shih‐Che; Lin, Ching‐Heng; Lee, I‐Te; H‐H Sheu, Wayne
Abstract: Aims/Introduction: Currently, the impact of hospital‐wide glycemic control interventions on length of hospital stay (LOS) and readmission rates are largely unknown. We investigated the impact of a 4‐year hospital‐wide remote glycemic management program on LOS and 30‐day readmission rates among hospitalized adults who received glucose monitoring. Materials and Methods: In this retrospective study, hospitalized patients who received glucose monitoring were classified into groups 1 (high glucose variability), 2 (hypoglycemia), 3 (hyperglycemia) and 4 (relatively stable). The monthly percentage changes, and average monthly percentage changes of hyperglycemia, hypoglycemia and treat to target were determined using joinpoint regression analysis. Results: A total of 106, 528 hospitalized patients (mean age 60.9 ± 18.5 years, 57% men) were enrolled. We observed a significant reduction in the percentage of inpatients in poor glycemic control groups (groups 1, 2 and 3, all P < 0.001), and a reciprocal increase in the relatively stable group (group 4) from 2016 to 2019. We found a significant reduction in LOS by 11.4% (10.5–9.3 days, P = 0.002, after adjustment for age, sex, and admission department). The 30‐day readmission rate decreased from 29.9% to 29.3%, mainly among those in group 4 in 2019 ( P < 0.001 after adjustment of sex, age, admission department and LOS). Conclusions: Improved glycemic control through a hospital‐wide electronic remote glycemic management system reduced LOS and 30‐day readmission rates. Findings observed in this study might be associated with the reduction in cost of avoidable hospitalizations.